The Design of a Smart Prototype Security System for Wildlife Conservation - Smita Francis; Tega Paulus (Science and Technology: Developments and Applications Vol. 8, 2025)
The exploitation of natural resources through poaching and plundering has a significant impact on the environment, society, economy, and culture. Namibia has recently witnessed a surge in wildlife crime, as evidenced by the reported poaching incidents in the iconic Etosha Game Park in 2022, where 61 black and 26 white rhinos were killed. Elephants, rhinos, and pangolins are currently the three main high-value targets for poachers due to their ivory, horns, scales, and flesh. Despite the Namibian government’s efforts to combat poaching, the illegal killing of wild animals persists, which negatively impacts natural diversity and the national tourism industry. This paper proposes an innovative, intelligent system to facilitate real-time detection and monitoring of wild animals and timely detection of poaching activities. The system is designed to assist national parks and private game parks in identifying and combating poaching in real-time by utilising off-the-shelf components.